Osteopontin deficiency aggravates hepatic injury induced by ischemia–reperfusion in mice - Patouraux, S (Nature Publishing Group, 2014)
Osteopontin (OPN) is a multifunctional protein involved in hepatic steatosis, inflammation, fibrosis and cancer progression. However, its role in hepatic injury induced by ischemia–reperfusion (I–R) has not yet been investigated. We show here that hepatic warm ischemia for 45 min followed by reperfusion for 4 h induced the upregulation of the hepatic and systemic level of OPN in mice. Plasma aspartate aminotransferase and alanine aminotransferase levels were strongly increased in Opn(−/−) mice compared with wild-type (Wt) mice after I–R, and histological analysis of the liver revealed a significantly higher incidence of necrosis of hepatocytes. In addition, the expression levels of inducible nitric oxide synthase (iNOS), tumor necrosis factor-α (TNFα), interleukin 6 (IL6) and interferon-γ were strongly upregulated in Opn(−/−) mice versus Wt mice after I–R. One explanation for these responses could be the vulnerability of the OPN-deficient hepatocyte. Indeed, the downregulation of OPN in primary and AML12 hepatocytes decreased cell viability in the basal state and sensitized AML12 hepatocytes to cell death induced by oxygen–glucose deprivation and TNFα. Further, the downregulation of OPN in AML12 hepatocytes caused a strong decrease in the expression of anti-apoptotic Bcl2 and in the ATP level. The hepatic expression of Bcl2 also decreased in Opn(−/−) mice versus Wt mice livers after I–R. Another explanation could be the regulation of the macrophage activity by OPN. In RAW macrophages, the downregulation of OPN enhanced iNOS expression in the basal state and sensitized macrophages to inflammatory signals, as evaluated by the upregulation of iNOS, TNFα and IL6 in response to lipopolysaccharide. In conclusion, OPN partially protects from hepatic injury and inflammation induced in this experimental model of liver I–R. This could be due to its ability to partially prevent death of hepatocytes and to limit the production of toxic iNOS-derived NO by macrophages.